O lúdico como estratégia de aprendizagem na educação infantil - FONSECA, Silvani de Lima (2023)
The present work is a bibliographical study whose theme is “Play as a learning strategy in early childhood education”, with the general objective of understanding playfulness as a didactic strategy in the teaching-learning process in early childhood education. As specific objectives: to raise historical and conceptual information about the ludic/ludicity; to verify how ludicity is used as a pedagogical strategy in the teaching and learning process in early childhood education; understand how playfulness can promote the improvement of early childhood education students' learning. The developed methodology involved a vast bibliographic survey on the subject, with the intention of building a theoretical basis in several authors such as Kishimoto (2013), Santos (2012), Ariès (1981), among others. The results, based on the reflections made, show that the use of playfulness as a didactic resource in early childhood education, if planned within a pedagogical strategy, will positively influence the children's teaching-learning process.